Reseña de: Murphy, Alexander B. (2020). Geografía. ¿Por qué importa? - Morales Yago, Francisco José (Espacio Tiempo y Forma. Serie VI, Geografía, 2020)
Reseña de: Murphy, Alexander B.  (2020). Geografía. ¿Por qué importa? Madrid: Alianza Editorial.  162 págs. ISBN- 978-84-9080-762-8.